CHARACTERISTICS OF ALLERGENS IN THE ASTHMATIC TRIAD - Kim Ekaterina Sergeevna (Bright Mind Publishing, 2025)
Aspirin bronchial asthma, aspirin or asthmatic triad (AT) is characterized by three main clinical manifestations - bronchial asthma (BA), polypous rhinosinusitis (PRS) and intolerance to aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs). Despite the fact that bronchial asthma in patients with AT makes up, according to various sources, from 10 to 20% of its clinical and pathogenetic variants, torpid course of the disease, risk of sudden death, sharp decrease in the quality of life of patients, classifies it as the most severe forms of BA. A distinctive feature of the disease is also the high cost of treatment and diagnostic measures. The relevance of the AT problem is evidenced by the fact that the European Coordination Committee was created to study it, and in 2022 - the International Society of Scientists, which coordinates research on the problem of PRS. According to medical statistics, out of 7 million patients with BA in Russia, 1 million have severe forms of the disease, of which 40% of patients are represented by AT or aspirin bronchial asthma. The asthmatic triad has been known to medical science for about 80 years, however, to this day it remains unclear what causes the severity, polymorphism and uniqueness of clinical manifestations of AT. Many issues of pathogenesis, clinical and diagnostic approaches have not yet been resolved and are discussed by allergists, immunologists, otolaryngologists, pulmonologists.